Sexism Ancient and Modern: Turning the Male World Upside Down - Bergin, Helen F. (Pacifica, 1990)
Sexism is about perception and identity. The starting point for this discussion is a brief consideration of how Biblical and later texts have perceived and portrayed women. If women have been shown, even unconsciously, in the guise others have desired, how is this to be prevented today? The authors argue that language and symbolism are always influential. The language we use to refer to God influences not only how we think of God, but also how we see ourselves. If we are wrestling today to find language and symbols that speak to us, we are indeed following a biblical tradition that did just that. Breaking free is not simply a matter of language, but a transference of power, to be shared by women and men together. Such a transference means shaking present models of perception in the search for an inclusive and just alternative.